2015
DOI: 10.1021/acs.iecr.5b02751
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalysis of Graphene and TiO2 Dual-Coupled Carbon Nanofibers Post-treated at Various Temperatures

Abstract: Graphene and titanium dioxide (TiO 2 ) were coupled to a conducting polymer substrate to generate graphene− TiO 2 carbon nanofibers (GTCNs) using an electrospinning method with a post-thermal treatment process. The photocatalytic activities of GTCNs for the purification of selected toxic organic pollutants under visible-light illumination were higher than those of three reference photocatalysts (i.e., TiO 2 -, graphene-, and polyacrylonitrile-based carbon nanofibers). The photocatalytic activities of GTCNs inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Electrospun nanofibers, as the forefront of advanced fibrous materials, combining the fine flexibility, low density, extremely high aspect ratio, ease of scalable synthesis from various materials, possessed favorable foreground applications in various fields [22][23][24]. As a result of their outstanding potential, many efforts had been made to use electrospun nanofibers for the preparation of CNFs@TiO 2 composites [1,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun nanofibers, as the forefront of advanced fibrous materials, combining the fine flexibility, low density, extremely high aspect ratio, ease of scalable synthesis from various materials, possessed favorable foreground applications in various fields [22][23][24]. As a result of their outstanding potential, many efforts had been made to use electrospun nanofibers for the preparation of CNFs@TiO 2 composites [1,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…22 A 4-fold increase of the degradation rate was observed and it was related both to the more-efficient electron transfer and to the affinity of the substrate to the GO and rGO sheets. In another study, Chun et al 23 reported the graphene and TiO 2 incorporation into carbon nanofibers and their performance under visible-LED irradiation: the initial concentration resulted as a crucial parameter for the photocatalytic treatment of gas-phase target pollutants. According to our previous work, 7,11 photocatalytic oxidation has been proven to be a promising technology for air purification, and nanostructured mats based on electrospun nanofibers offer a proper support in the production of active filtering media in order to combine the physical activity of the media with the chemical degradation of harmful pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Just a few papers refer to gas-phase experiments, and before focusing on them, it is very important to observe that, in gas-phase photocatalysis, the dominant photodegradation mechanism is not always straightforward and, more generally, a myriad of radical-based reactions are potentially available. Moreover, it must be emphasized that the local environment, as well as the target species, govern all these reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their large specific surface area, high porosity, and tunable mechanical properties, nanofibers have broad application in many fields, including bioengineered structures, air and water filtration, electronics, drug delivery, fuel cells, biomedical tissue engineering, building materials, and smart clothing . However, nanofibers produced by traditional methods present some problems, including their toxic solvents and low output.…”
Section: Introductionmentioning
confidence: 99%